REAKSI PASAR TERHADAP PENGUMUMAN DIVIDEN DI BURSA EFEK INDONESIA - Pramana, Ketut Satya; Abundanti, Nyoman (E-Jurnal Manajemen, 2017)
The development of the growing world economy is caused by the linkage of the economic actors in it and one of them is the company that plays an active role in the economic development of Indonesia . This study aims to analyze market reaction to the announcement of dividend in Indonesia Stock Exchange . The population in this study is the company that announced its dividend in the period 2015 . The method used in determining the sample is the quota sampling method and obtained as many as 45 issuers that meet the quota sampling criteria . Tests in this study using event study approach   with the analysis techniques used to test the level of significant abnormal return is the test t-test . The result that can be obtained from this research is the market reacts negatively at the time of dividend announcement with period of time (day t-7 until day t + 7) with marked not significant abnormal return. The results can be interpreted that the dividend announcement has no information content and is not considered important information for investors.